Analisis Kriminologi Budaya atas Peran Media dalam Kontestasi Makna selama Putaran Kedua Pilkada DKI Jakarta 2017 - Abdel Rama (Jurnal Kriminologi Indonesia, 2019)
The phenomenon of the 2017 DKI Jakarta Regional Head Election (Pilkada) presents a lot of friction which causes a contestation of meanings to be analyzed using a cultural criminology point of view. Having a focus on one word, namely “eviction”, cultural criminology is placed as the basis for analysis of contestation that focuses on cultural space and the influence of post-modernism. Cultural criminology also discusses how education plays a major role in shaping the discourse construction process of crime. In addition, cultural criminology also acts as an eye-opener and a bag of tricks in analyzing the discourse of crime.Keywords: Cultural criminology, media, meaning contestation